THE IMPACT OF DIGITAL TV BROADCASTS ON VIEWING BEHAVIOR OF THE COMMUNITY OF BANDAR LAMPUNG CITY - Azzahra SR, Rizka Annisa; Dukhi, Rizki; Julianto, Ribut; Sasora, Fajar (Journal of Public Relations and Digital Communication (JPRDC), 2023)
This research aims to investigate the impact of digital TV broadcasts on people's viewing behavior in Bandar Lampung City. Along with technological developments, the transition from analog television broadcasts to digital television broadcasts has occurred in many areas, including the city of Bandar Lampung. Understanding how these shifts affect people's viewing behavior is important to inform decision making and the development of future television broadcast strategies. Research reveals several challenges faced by society in adapting to digital TV broadcasts. These challenges include changing viewing habits, the need to acquire digital TV reception equipment, and accessibility gaps related to geography and infrastructure. This research provides an important contribution in understanding the impact of digital TV broadcasts on the viewing behavior of the people of Bandar Lampung City. The results of this research can be a valuable source of information for television broadcast organizers in developing relevant content strategies and improving people's viewing experience. Apart from that, these findings can also provide input to local governments in efforts to increase accessibility and support community adaptation to the transition to digital TV broadcasts.